2018
DOI: 10.3892/mmr.2018.9265
|View full text |Cite
|
Sign up to set email alerts
|

SH2B1 protects against OGD/R‑induced apoptosis in PC12 cells via activation of the JAK2/STAT3 signaling pathway

Abstract: Apoptosis acts as the primary pathogenesis of cerebral ischemia/reperfusion (I/R) injury. Prior studies have revealed the effects of src homology 2 (SH2)B adaptor protein 1 (SH2B1) in myocardial infarction; however, involvement of SH2B1 in cerebral I/R injury and the underlying mechanisms remain to be investigated. In the present study, neural-like PC12 cells underwent 6 h of oxygen-glucose deprivation (OGD) followed by 24 h of reoxygenation (OGD/R). PC12 cells were pre-transfected with an adenovirus encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…A series of papers have been published that uncovered the role of SH2B1 in the occurrence, progression, and worsening of colorectal cancer, gastric cancer, and NSCLC. 19 , 27 , 29 In conclusion, we identified a novel biomarker of the EC progression circRNA hsa_circ_0075960, which served as a sponger of miR-361-3p to regulate the expression of SH2B1.…”
Section: Discussionmentioning
confidence: 90%
“…A series of papers have been published that uncovered the role of SH2B1 in the occurrence, progression, and worsening of colorectal cancer, gastric cancer, and NSCLC. 19 , 27 , 29 In conclusion, we identified a novel biomarker of the EC progression circRNA hsa_circ_0075960, which served as a sponger of miR-361-3p to regulate the expression of SH2B1.…”
Section: Discussionmentioning
confidence: 90%
“…A further reduction in cell viability was found 24 h after reperfusion in cells subjected to 6 h OGD, and that are therefore considered an ideal model of I/R injury in vitro [ 17 ]. Similarly, 6 h OGD followed by 24 h reperfusion reduced cell viability to ~50% and increased LDH release to ~35% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PC12 cell, neuronal apoptosis may be due to different apoptotic pathways: intrinsic or extrinsic for example [44]. Previous study reported that PC12 cells from OGD/R injury partially by the JAK2/STAT3dependent inhibition of apoptosis, which provided a novel therapeutic target for the treatment of cerebral I/R injury [45].…”
Section: Discussionmentioning
confidence: 99%